Acute and Long-Term Effects of Aortic Compliance Decrease on Central Hemodynamics: A Modeling Analysis - Pagoulatou, Stamatia; Adamopoulos, Dionysios; Rovas, Georgios; Bikia, Vasiliki; Stergiopulos, Nikolaos (Frontiers in Physiology, 2021)
Aortic compliance is an important determinant of cardiac afterload and a contributor to cardiovascular morbidity. In the present study, we sought to provide in-silico insights into the acute as well as long-term effects of aortic compliance decrease on central hemodynamics. To that aim, we used a mathematical model of the cardiovascular system to simulate the hemodynamics a) of a healthy young adult (baseline), b) acutely after banding of the proximal aorta, c) after the heart remodeled itself to match the increased afterload. The simulated pressure and flow waves were used for subsequent wave separation analysis. Aortic banding induced hypertension (SBP 106 mmHg at baseline vs 152 mmHg after banding), which was sustained after LV remodeling. The main mechanism that drove hypertension was the enhancement of the forward wave, which became even more significant after LV remodeling (forward amplitude 30 mmHg at baseline vs 60 mmHg acutely after banding vs 64 mmHg after remodeling). Accordingly, the forward wave’s contribution to the total pulse pressure increased throughout this process, while the reflection coefficient acutely decreased and then remained roughly constant. Finally, LV remodeling was accompanied by a decrease in augmentation index (AIx 13% acutely after banding vs -3% after remodeling) and a change of the central pressure wave phenotype from the characteristic Type A (“old”) to Type C (“young”) phenotype. These findings provide valuable insights into the mechanisms of hypertension and provoke us to reconsider our understanding of AIx as a solely arterial parameter.